2017
DOI: 10.3382/ps/pex046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stunning frequency and current waveform in poultry welfare and meat quality

Abstract: This study aimed to evaluate the effects of different stunning frequencies and electrical current waveforms on chicken welfare and meat quality. Two-hundred-thirty-two Cobb broilers, 48 d of age and 2.76 ± 0.47 live-weight, were randomly assigned into 4 stunning treatments - 2 frequencies (300 Hz and 650 Hz) and 2 current waveforms (direct current [DC] and alternating current [AC]). Broilers were electrically stunned in a water bath in a commercial slaughterhouse (70 V, 100 mA). The electronarcosis and stunnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…Takahashi [ 42 ] reported higher WHC in breast meat of broilers stunned with high frequencies. Our results, in line with findings of Siqueira [ 33 ] and Karunanayaka [ 31 ], confirm that PMD breast samples have lower WHC than normal ones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Takahashi [ 42 ] reported higher WHC in breast meat of broilers stunned with high frequencies. Our results, in line with findings of Siqueira [ 33 ] and Karunanayaka [ 31 ], confirm that PMD breast samples have lower WHC than normal ones.…”
Section: Discussionsupporting
confidence: 92%
“…Among signs of stunning ineffectiveness, the presence of corneal reflex was the most frequently detected in this study. By using lower frequencies, other authors reported higher percentages of animals with a positive corneal reflex [ 22 , 33 ]. The eye reflex was recognized by several authors as the physical reflex most reliable in evaluating unconsciousness [ 10 , 11 ], although its absence does not necessarily indicate the absence of pain.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, this relates to better body composition, higher breast meat yield and lower abdominal fat. Animal (poultry) welfare concerns have gained importance by many actors in the meat chain such as consumers, producers, and retailers of animal-based food products, mainly in the European Union (Lambooij et al, 2014;Siqueira et al, 2017). Speaking about the farmers' role and a potential lack of awareness of the attributes that are mostly demanded by consumers, this issue can lead to missing the focus of their efforts, which, in turn, means that quality is not deployed to generate downstream value in the meat chain (Simons et al, 2003).…”
Section: Qfd In the Chicken Meat Chainmentioning
confidence: 99%
“…Lactate concentration was determined by using the lactate oxidase method (Lactate Liquiform, Labtest Diagnóstica S.A.), according to Siqueira et al, [26]. Briefly, 100 mg of muscle samples frozen in liquid nitrogen were homogenized in 20 mM citrate-50 mM phosphate buffer, EDTA 2.5mg/ml pH 6.8.…”
Section: Lactate (La) Determinationmentioning
confidence: 99%